Human methicillin-sensitive Staphylococcus aureus biofilms: potential associations with antibiotic resistance persistence and surface polysaccharide antigens - Babra, C.; Gogoi Tiwari, Jully; Costantino, Paul; Sunagar, R.; Isloor, S.; Hegde, N.; Mukkur, Trilochan (Wiley, 2013)
The development of persistent antibiotic resistance by human methicillin-sensitive Staphylococcus aureus (MSSA) strains and substantial association with poly-N-acetyl glucosamine (PNAG) in biofilms is reported in this investigation. Sixteen of 31 MSSA strains under study were found to have developed resistance to one or more antibiotics, with four strains, two of which did not produce biofilms, showing resistance to cefoxitin, undetectable by mecA amplification. Antibiotic resistance displayed by 13/14 biofilm-forming S. aureus isolates remained persistent for 4 weeks prior to reverting back to the original antibiotic susceptibility, prompting a suggestion of determining antibiograms for clinical S. aureus isolates subcultured from biofilms developed in vitro as well as planktonic subcultures prepared from the site of infection. While there was correlation of antibiotic resistance with biofilm formation confirming previous reports, this is the first time that persistence of the biofilm-associated antibiotic resistance by S. aureus as planktonic cells is reported. Among the two methods used for assessment of biofilm formation, the tissue culture plate (TCP) method revealed that almost all strains were strong or moderate biofilm producers whereas only 19/31 strains were biofilm producers using the Congo Red agar (CRA) method indicating the superiority of the TCP method in detecting biofilm producers. We alsoobserved no association between biofilm formation and major capsule types. However, substantial, although not absolute, association of biofilm formation with PNAG was observed, warranting continued identification of additional surface-associated polysaccharide and/or protein antigens associated with biofilm formation for development of an effective vaccine against S. aureus infections regardless of capsular phenotype.